Pravastatin and C reactive protein modulate protease- activated receptor-1 expression in vitro blood platelets - Chu, L-X; Zhou, S-X; Yang, F; Qin, Y-Q; Liang, Z-S; Mo, C-G; Wang, X-D; Xie, J; He, L-P (Cellular and Molecular Biology, 2016)
Protease-activated receptor-1 (PAR-1) plays an important role in mediating activation of human platelets by thrombin. However, mechanism of statin in ADP-induced platelet PAR-1 expression is also unknown. Aggregometry, flow cytometry, immunoblotting and ELISA were used to determine role of pravastatin participating in ADP-induced platelet activation and PAR-1 expression. ADP stimulation significantly increased PAR-1 expression on platelets. PAR-1 antagonist SCH-79797 inhibited platelet aggregation as well as decreased platelet P-selectin expression induced by ADP. CRP inhibited PAR-1 expression induced by ADP in a concentration-dependent manner. Pravastatin treatment reduced PAR-1 expression in a concentration-dependent manner. Combination treatment of CRP and Pravastatin significantly reduced platelet PAR-1 expression induced by ADP. By western-blot analysis, pravastatin treatment did not influence total PAR-1 after ADP treatment. CRP decreased platelet total PAR-1 expression induced by ADP. Pravastatin and CRP reduced TXB2 formation by ADP significantly. CRP decreased thrombin fragment F1+2 level with ADP treatment. Pravastatin, in contrast, did not influence F1+2 level. Upon treatment with Pravastatin reduced platelet LOX-1 expression induced by ADP. In conclusion, PAR-1 served as a critical mechanism to relay platelet activation process induced by ADP. CRP and pravastatin reduce PAR-1 expression in platelet by ADP pathway.